Disentangling the sources of pro-social behavior in the workplace : a field experiment - Mirco Tonin; Michael Vlassopoulos (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper presents evidence from a field experiment, which aims to identify the two sources of worker's pro-social motivation that have been considered in the literature: action-oriented altruism and output-oriented altruism. To this end we employ an experimental design that first measures the level of effort exerted by student workers on a data entry task in an environment that elicits purely selfish behavior and we compare it to effort exerted in an environment that also induces action-oriented altruism. We then compare the latter to effort exerted in an environment where both types of altruistic preferences are elicited. We find that action-oriented altruism accounts for a significant increase in effort, while there is no additional impact due to output-oriented altruism. We also find significant gender-related differences in the treatment effect: women are very responsive to the treatment condition eliciting action-oriented altruism, while men's behavior is not affected by any of the treatments.
Keywords: C93; D64; J16; 330; pro-social behavior; field experiment; effort; charitable donations; Arbeitswelt; Arbeitsplatz; Soziales Verhalten; Altruismus; Feldforschung